Conformational Dynamics of DNA Polymerases Revealed at the Single-Molecule Level - Millar, David P. (Frontiers in Molecular Biosciences, 2022)
DNA polymerases are intrinsically dynamic macromolecular machines. The purpose of this review is to describe the smFRET methods that are used to probe the conformational dynamics of DNA polymerases, focusing on E. coli DNA polymerase I. The studies reviewed here reveal the conformational dynamics underpinning the nucleotide selection, proofreading and 5' nuclease activities of Pol I. Moreover, the mechanisms revealed for Pol I are likely employed across the DNA polymerase family. smFRET methods have also been used to examine other aspects of DNA polymerase activity.